MENINGKATKAN KETERAMPILAN DASAR BAHASA INGGRIS DENGAN APLIKASI YUREKA KEPADA MAHASISWA DAN PELAJAR ASRAMA DAMAL - Paskalis Kaipman; Selmina Rumawak; Demmy Tabuni; Ivona Dorobia; Onisimus Faot (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity (PKM) aims to provide education on "How to Improve Basic English Skills" for students and pupils at the Damal Dormitory, Perumnas I Waena, Jayapura. These students and pupils study and attend various universities and schools in Jayapura. Based on our observations, they need basic education about English and motivation to learn English, therefore we are conducting community service. This community service uses an interactive approach, mentoring and the use of digital media where lecturers give lectures and one-day training that focuses on basic English skills, such as the importance of English, how to learn English and a learning platform that can be used, namely the Yureka application. After basic English education is given to the students and pupils who attend, there are lecturers who guide and mentor participants starting from how to access the Playstore on their cellphones, download the Yureka application, install the application and finally how to use it. In the Yureka application, participants learn basic English such as idioms and TOEFL vocabulary